Elevational ranges of pioneer marsh species are site specific and likely shaped by different abiotic and biotic factors - Charlotte S. Steinigeweg; Ole J. Siebeneicher; Boris Schröder; Michael Kleyer; Kertu Lõhmus; Swantje Löbel (Ecosphere)
Abstract Salt marshes are dynamic systems whose landscape structure and resilience to disturbance depend on bio‐geomorphological interactions. The ecological niches of salt marsh plants are asserted to be organized along an elevational gradient, determining the impact of abiotic factors such as soil aeration, flooding, and salinity, which generate the typical salt marsh zonation. In the foremost (pioneer) zone, vegetation must cope with nonoptimal environmental conditions due to strong impacts of hydrodynamic forces and sedimentation and is threatened by climate change–induced sea level rise or increased storminess. To test the hypothesis that species have different elevational ranges, which are shaped by local abiotic conditions and biotic interactions, salt marsh species occurrences and covers were recorded along 65 seaward–landward transects at two study sites on the back‐barrier island Spiekeroog in the German Wadden Sea, differing in topography, site age, and history. Elevations were extracted from a digital terrain model. Zero‐inflated beta regression models demonstrated that species occurrence and cover are mediated by elevation in a species‐specific manner. The fast colonizer Salicornia procumbens occurred foremost at the lowest elevations, followed by the pioneer species Spartina anglica and Salicornia europaea. The higher marsh species Limonium vulgare, Atriplex portulacoides, and Spergularia spp. occurred at higher elevations, indicating varying species' vulnerability to local abiotic factors. Furthermore, the individual cover of species was negatively related to the total cover of other species, possibly indicating that species‐specific elevational ranges are further modified by interspecific interactions. Especially, the cover of the ecosystem engineer Sp. anglica mostly had negative effects on individual species cover, although positive effects on the cover of Sa. europaea at the eastern site. Our results provide insights into plant species responses and interactions under highly dynamic conditions in the foremost marsh zone. Knowledge about species‐specific responses to their abiotic and biotic environment is an important prerequisite for modeling and predicting future ecosystem shifts in salt marshes under climate change.